2001
DOI: 10.1074/jbc.m009250200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Alkaline Phosphatase from Human Placenta at 1.8 Å Resolution

Abstract: Human placental alkaline phosphatase (PLAP) is one of three tissue-specific human APs extensively studied because of its ectopic expression in tumors. The crystal structure, determined at 1.8-Å resolution, reveals that during evolution, only the overall features of the enzyme have been conserved with respect to Escherichia coli. The surface is deeply mutated with 8% residues in common, and in the active site, only residues strictly necessary to perform the catalysis have been preserved. Additional structural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
172
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(176 citation statements)
references
References 31 publications
2
172
0
2
Order By: Relevance
“…Data recently reported for bovine intestinal alkaline phosphatase has shown that enzyme adsorption also occurs through the GPI anchor and that the major axis of the aminoacid moiety is parallel to the adsorption surface [15,[28][29][30]; they are in good agreement with our results. According to several authors, the anchor should be located opposite the catalytic site, on the face parallel to the major axis of the enzyme [30,56]. Consequently, DSAP is oriented with its major axis almost parallel to the interface.…”
Section: Proposed Model For Plsap and Dsap-lb Film Interactionmentioning
confidence: 99%
“…Data recently reported for bovine intestinal alkaline phosphatase has shown that enzyme adsorption also occurs through the GPI anchor and that the major axis of the aminoacid moiety is parallel to the adsorption surface [15,[28][29][30]; they are in good agreement with our results. According to several authors, the anchor should be located opposite the catalytic site, on the face parallel to the major axis of the enzyme [30,56]. Consequently, DSAP is oriented with its major axis almost parallel to the interface.…”
Section: Proposed Model For Plsap and Dsap-lb Film Interactionmentioning
confidence: 99%
“…1B). As the general shape of the protein may be assimilated to a 10 × 5 nm prolate ellipsoid of revolution [10], this molecular area is consistent with a protein oriented with its major axis parallel to the interface as defined by Narsimhan and Uraizee [49]. Actually, the protein area is then 40 nm 2 but some empty space has to be considered between AP molecules.…”
Section: Interfacial Molecular Organization Of Ap-gpimentioning
confidence: 89%
“…The structure of AP from human placenta, which presents about 90% sequence similarity with intestinal AP, has been solved by X-rays [10]. Each monomer shows a typical α/β topology with β-sheets at the center surrounded by α-helices oriented approximately in the same direction.…”
Section: Introductionmentioning
confidence: 99%
“…The protein encoded by ALPL contains 5 important domains [17,18]: activation domain, N-terminal coiled region, homodimer, crown domain and calcium binding site. Mutations around these sites may affect the activity of the protein.…”
Section: Discussionmentioning
confidence: 99%